(untitled) (Journal of Finance, Business and Management Studies, 2024)
Online Network Digital Commerce (ONDC) is a revolutionary e-commerce platform that offers a new perspective on business and consumer interactions. This conceptual paper provides a concise overview of ONDC, touching upon its key attributes, disruptive potential, challenges, opportunities for marketers, and expected growth. Its core attributes include interoperability, accessibility, and inclusivity, making it an inclusive platform for businesses of all sizes. ONDC is a catalyst for Micro, Small, and Medium Enterprises (MSMEs), providing equal access to digital commerce opportunities. Its disruptive potential is substantial, as it aims to challenge existing e-commerce platforms by reducing their power and promoting competition. This model envisions a more level playing field and increased consumer choice. For marketers, ONDC presents opportunities to reach consumers and foster growth. It also empowers local businesses and entrepreneurs, potentially stimulating economic growth in a rapidly developing economy. With anticipated growth over the next five years, ONDC is poised to revolutionize the digital commerce landscape in India. However, the potential for ONDC to disrupt established players like Swiggy and Zomato in the online food delivery sector raises questions about its potential impact. In conclusion, ONDC is a game-changing innovation in Indian e-commerce, potentially empowering MSMEs, inspiring marketers, and fueling economic expansion.